HASIL BELAJAR PENGUKURAN BERAT DENGAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) - Butet, Hartati (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research problem faced is based on the fact on the field that teacher used is still conventionally where the teacher is centered of learning, fact the student result in learning standart of weight not as we hape. Fact the attitude above, reguired to be performed action with the learning model of Realistic Matematics Education (RME) that make student as the centered of learning (student centered).   This research a im to improve, repair study process in class, which is finally can inprove standart of weight learning process. This research is classroom action (PTK) by using qualitative and quantitative approach. Based on the research result, this model of learning Realistic Matematics Education (RME) can in rease the students standart of weight learning result. Mathe matize of everyday experience. Kata Kunci : hasil belajar; meansurment of weight; pendekatan rme.